Mapping System Design of a Genetic Mapping System for the White Nest Swallow (Collocalia Fuciphaga) in Java - Utomo, Budi; Ramadhani, Risky Aswi; Firliana, Rina; Tanjungsari, Ardina; Kasih, Patmi ((JAIS) Journal of Applied Intelligent System, 2024)
The distribution of the white swift (Collocalia fuciphaga) is on several large islands in Indonesia. The white swallow has an advantage over the nests of the black swallow and sriti, having edible parts reaching 85-100% of the total nest. Many types of white swallow's nests in Indonesia are known for their different physical characteristics, color and weight. It is not known that these differences occur due to genetic differences or simply due to differences in the type of food and living environment. Differences due to food and environmental factors do not really affect the health function of the nest. Differences due to genetics greatly influence the function of the nest for health. The design of this system is initial research to start mapping white nest swiftlets in Indonesia. The results of the design will be used as a data storage system for genetic mapping of white nest swallows on the island of Java by taking DNA samples of swallows from various habitat areas. The system will store data on habitat areas, record location points and take bird samples from these areas to then carry out laboratory tests to determine the DNA code test of each bird sample. Furthermore, it is hoped that clear genetic mapping results can be used to determine the quality and function of the bioactive components of white swift nests on the island of Java. The mapping results will also be a source of knowledge about the richness of the germplasm of native Indonesian swiftlets. Keywords: GIS, Bioactive, genetic, Java, mapping, white swallow's nest